التراث الفلسفي الإسلامي: وماذا يمكن أن يقدمه لحاضر الحضارة الإنسانية ومستقبلها؟: Islamic Philosophical Tradition: What Can be Contributed to the Present and Future of Human Civilization? - Mohamed Meerasahibu, Dheen Mohamed (Afkar: Jurnal Akidah dan Pemikiran Islam, 2019)
Islamic Philosophy - defined variously by Muslim scholars - has had tremendous influence on human history, more particularly so on Western history of ideas and philosophies. Through its various manifestations - Kalām, Sufism, peripatetic philosophy and many other areas of thinking such as sociology, psychology etc. – it has left a lasting influence on Islamic societies and the development of its thought manifested in various schools. A review of the bibliographies of studies around Muslim philosophy demonstrates that most of the studies conducted by Muslims and others from the West or East have been about its past history and the contribution it has had on the Medieval West. In most Western writings it was characterized as a phase of western intellectual history and rather unfortunately Muslims started towing the same line. In the meanwhile, very little serious attention was paid to the possible relevance of this philosophy to contemporary man. This paper, endeavours to point to four areas in which philosophy can seriously contribute to the intellectual discourse of contemporary human societies largely characterized by uncertainties and perplexities. It also aims at outlining the way forward by taking philosophy back to the ‘Divine world view’ that should govern the philosophical thinking, and providing it with an understanding of necessary cooperation between faith and knowledge that insists on the ethical dimension of philosophical inquiry. The Dialectic of “me and the other”, which is a very serious issue that the modern man is struggling with, is another area where Islamic philosophy can make an immense contribution that will help the present man and his future.